CLINICAL EPIDEMIOLOGY OF INTESTINAL INFECTIONS AND YERSINIOSIS - Ostonova Gulrukh Sodikovna (World Scientific Research Journal, 2025)
Abstract: Yersiniosis is a disease caused by several types of enteropathogenic Yersinia. It has an alimentary transmission route and manifests clinically with CNS intoxication, dyspepsia, tonsillitis, lymphadenopathy, rash, and organ damage in various organs. Data from the examination, diagnosis, and treatment of 120 children aged 6 months to 14 years suffering from acute diarrheal disease from 2021 to 2023 were analyzed. While they formed the main study group, 40 children were examined as a control group. All observed children underwent extensive continuous examinations, including clinical, laboratory, biochemical, virological, and immunological studies. Special attention was paid to their complaints, past and concomitant diseases, causes of illness, duration of illness, and results of diagnostic and early therapeutic measures.